Hubungan Pola Makan dengan Hipertensi pada Populasi Pedesaan: Sebuah Tinjauan Cakupan - Aliyah, Ira Nur; Nugraha, Bambang Aditya; Fitri, Siti Ulfah Rifa’atul (Jurnal Keperawatan Florence Nightingale, 2025)
The global prevalence of hypertension has shown a consistent increase, including in rural areas, which generally have limited access to health services, nutrition education, and resources for non-communicable disease prevention. Changes in consumption patterns due to modernization have exacerbated exposure to dietary risk factors, particularly high intakes of salt, saturated fat, added sugar, and low fiber consumption. As a modifiable risk factor, diet plays a crucial role in hypertension control, yet scientific evidence in rural populations remains scattered and has not been systematically synthesized. Therefore, this study aimed to map scientific evidence on the relationship between diet and hypertension in rural populations through a scoping review approach. A search was conducted in PubMed, Scopus, Science Direct, and Cambridge Core using the PICOS framework for publications from 2020-2025. Of the 21,045 articles, 10 met the inclusion criteria based on PRISMA-ScR and JBI quality assessment (score ≥75%). The results showed that the majority of studies found a significant association between unhealthy diet and hypertension, particularly when accompanied by obesity and a pro-inflammatory diet. Factors such as physical activity, culture, and nutritional status also influence this association. These findings underscore the importance of locally tailored community nutrition interventions and promotion of anti-inflammatory diets to prevent hypertension in rural areas.